SOME BIOLOGICAL NOTES ON BARILIUS BENDELISIS (HAMILTON) - Grower, S P (Indian Journal of Fisheries, 2011)
Barilius bendelisis (Hamilton) is a fish highly known for its food value in Dehra Dun, Uttar Pradesh. The survey work done by Hora and Mukerjee (1936), Lai and Chatterjee (1962), Singh (1964) and Grover(1970) in the Doon waters did not include any ecological studies of the existing ichthyofauna. Observations of the author on the food, breeding and development of B. bendelisis in the Doon waters are presented in this short communication. Observations were made every three